2017
DOI: 10.1051/parasite/2017002
|View full text |Cite
|
Sign up to set email alerts
|

Canine visceral leishmaniasis in the metropolitan area of São Paulo:Pintomyia fischerias potential vector ofLeishmania infantum

Abstract: American visceral leishmaniasis is a zoonosis caused by Leishmania infantum and transmitted mainly by Lutzomyia longipalpis. However, canine cases have been reported in the absence of this species in the Greater São Paulo region, where Pintomyia fischeri and Migonemyia migonei are the predominant species. This raises the suspicion that they could be acting as vectors. Therefore, this study sought to investigate specific vector capacity parameters of these species and to compare them with those of Lu. longipalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 37 publications
1
19
0
5
Order By: Relevance
“…For a long time, only Phlebotomus were considered able to transmit these parasites in the Old World (Killick‐Kendrick, ), although the role of the genus Sergentomyia , too long ignored, cannot be neglected as a potential vector (Maia & Depaquit, ). Hence, additional research must persevere because, in some foci, unexpected vectors have been demonstrated; for example, in the Middle East (Svobodova et al ., ) or in Brazil (Galvis‐Ovallos et al ., ). The demonstration of such a transmission should not be based only on a polymerase chain reaction, which shows the carrying of parasitic DNA by sand flies.…”
Section: Discussionmentioning
confidence: 97%
“…For a long time, only Phlebotomus were considered able to transmit these parasites in the Old World (Killick‐Kendrick, ), although the role of the genus Sergentomyia , too long ignored, cannot be neglected as a potential vector (Maia & Depaquit, ). Hence, additional research must persevere because, in some foci, unexpected vectors have been demonstrated; for example, in the Middle East (Svobodova et al ., ) or in Brazil (Galvis‐Ovallos et al ., ). The demonstration of such a transmission should not be based only on a polymerase chain reaction, which shows the carrying of parasitic DNA by sand flies.…”
Section: Discussionmentioning
confidence: 97%
“…longipalpis, is absent, as well as the finding of other sand flies naturally infected with this agent have suggested that there are other vectors in Latin America (Table 2) (de Araújo-Pereira et al, 2010;Belo et al, 2013b;Bejarano et al, 2001;Carvalho et al, 2010;Feliciangeli et al, 1999;Galvis-Ovallos et al, 2017;González et al, 2014;Guimarães et al, 2016;Lainson and Rangel, 2005;Missawa et al, 2011;Moya et al, 2015Moya et al, , 2017Paternina-Gómez et al, 2013;Pita-Pereira et al, 2008;Rodrigues et al, 2016;Romero and Boelaert, 2010;Salomón et al, 2010;Travi et al, 1990;Zerpa et al, 2003); however, for only some of them has vectorial capacity been proven (Saraiva et al, 2009(Saraiva et al, , 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pintomyia fischeri was one of the most abundant species (41.62%) found in all 5 parks. In addition to its possible role in the transmission of L. (V.) braziliensis, this species is susceptible to infection by, and is a potential vector of, Leishmania infantum (Nicolle 1908), the etiologic agent of visceral leishmaniasis (Diniz et al 2014, Galvis-Ovallos et al 2017. Migonemyia migonei was found in very low abundance, but it is a species of epidemiological importance, which has been recently defined by Guimarães et al (2016) In addition to being considered a vector of L. (V.) braziliensis in various regions of Brazil, the 3rd epidemiologically important species, Ny.…”
mentioning
confidence: 99%